2016
DOI: 10.5312/wjo.v7.i12.793
|View full text |Cite
|
Sign up to set email alerts
|

Fifth metatarsal fractures and current treatment

Abstract: Metatarsal fractures are one of the most common injuries of the foot. There has been conflicting literature on management of fifth metatarsal fractures due to inconsistency with respect to classification of these fractures. This article provides a thorough review of fifth metatarsal fractures with examination of relevant literature to describe the management of fifth metatarsal fractures especially the proximal fracture. A description of nonoperative and operative management for fifth metatarsal fractures acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…16). 78 Operative fixation may also be considered for athletes with immediate stabilization and earlier return to play. Fifth metatarsal proximal diaphysis stress fractures typically do not heal well secondary to poor blood supply.…”
Section: Forefoot Fracturesmentioning
confidence: 99%
“…16). 78 Operative fixation may also be considered for athletes with immediate stabilization and earlier return to play. Fifth metatarsal proximal diaphysis stress fractures typically do not heal well secondary to poor blood supply.…”
Section: Forefoot Fracturesmentioning
confidence: 99%
“…La elección del tratamiento no quirúrgico se debe basar en el paciente y el tipo de fractura individual 25 . El tratamiento conservador se asocia, por lo general, con tiempos de curación ósea más largos, aunque evita los riesgos y las molestias de una cirugía 20,26,27 .…”
Section: Tratamiento Conservadorunclassified
“…1,3,4,[7][8][9][10][11][12] Since 1984, Torg et al's 13 recommendation of conservative treatment for Jones fractures, with a non-weight bearing cast for a period of 3 to 12 weeks, has been frequently followed. 5,10,12 In 2017, Brogan et al 14 concluded that all fifth metatarsal fractures can be safely managed with immediate full weight-bearing in an orthotic boot without adverse effects and that often no long-term review is needed. Most experts agree, however, that if the injury involves a displaced bone, multiple breaks, or fails to adequately heal, then surgery may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…Most experts agree, however, that if the injury involves a displaced bone, multiple breaks, or fails to adequately heal, then surgery may be needed. [1][2][3]5,12,15 Metatarsal fractures might result in alterations of walking. Bauer et al 16 reported gait asymmetry in 11 out of 20 patients with fifth metatarsal fractures, most with no visible gait disorder.…”
Section: Introductionmentioning
confidence: 99%